Prevalence of Metabolic Syndrome in Pre and Postmenopausal Women in Mogadishu-A Cross-Sectional Study - Ahmed Muhammad Bashir; Nur Rashid Ahmed; Mohamed Abdullahi Mohamed; Abdirizak Ali Isse; Hawa Osman Jimale; Ahmed Abdiaziz Mohamed; Mohamed Abdialim Ahmed (Liaquat National Journal of Primary Care)
This study aims to assess the prevalence of metabolic syndrome in women living in Mogadishu, Somalia, pre and post-menopause. A cross-sectional study was conducted on a sample of 138 women who were receiving medical care in internal medicine clinics in three hospitals located in Mogadishu, Somalia. The sample consisted of women who were both pre- and postmenopausal. Participants were assessed for metabolic syndrome according to the criteria established by the National Cholesterol Education Program’s Adult Treatment Panel III (NCEP-ATP III). The occurrence of metabolic syndrome in premenopausal women was 34% (47 out of 138), but in postmenopausal women, it was 100% (91 out of 91) (p<0.001). Postmenopausal women diagnosed with metabolic syndrome exhibited a notable rise in waist circumference, fasting blood glucose, blood pressure, and lipid levels. Conversely, their levels of HDL cholesterol experienced a significant reduction (p<0.001). Metabolic syndrome is often seen among women in Mogadishu, Somalia, both before and after menopause. Nevertheless, there is an increased probability of developing this condition in women who have reached menopause. Additional investigation is necessary to elucidate the underlying mechanisms that lead to the increased prevalence of metabolic syndrome in this particular population.